Compressive strength of connectors with different areas in three-unit polychromatic monolithic zirconia fixed partial dentures - Gomez Pacheco, Williams Gregory (2026)
Objective: To compare the compressive strength of connectors with different areas in three-unit fixed partial dentures (FPDs) fabricated from three types of polychromatic monolithic zirconia using CAD/CAM technology. Materials and methods: An in vitro experimental study was conducted with 30 FPD samples fabricated from three brands of polychromatic monolithic zirconia: IPS e.max® ZirCAD MT Multi (Ivoclar Vivadent; Schaan, Liechtenstein), KatanaTM Zirconia Super Translucent Multi Layered (STML) (Noritake Dental Supply; Okayama, Japan), and Ceramill® Zolid fx Multilayer (Amann Girrbach; Koblach, Austria). For each brand, 10 specimens were fabricated and subdivided into two subgroups according to connector area: 9 mm2 (n = 5) and 12 mm2 (n = 5). The specimens were subjected to compressive strength testing in a universal testing machine (CMT-5L, LG; Anyang, South Korea), applying a vertical load at the center of the pontic until fracture occurred. The obtained data were analyzed using the Kruskal-Wallis and Mann-Whitney U tests. Results: The 12 mm2 connectors showed significantly greater compressive strength than the 9 mm2 connectors, regardless of the brand used (medians of 1557.76 N [IQR: 425.54 N] vs. 1180.40 N [IQR: 708.32 N]; p = 0.024). KatanaTM Zirconia STML and IPS e.max® ZirCAD MT Multi zirconia achieved higher strength values than Ceramill® Zolid fx Multilayer for both connector sizes (p < 0.05). Conclusions: Connector area significantly influenced the compressive strength of polychromatic monolithic zirconia FPDs. The 12 mm2 connectors exhibited greater strength, and KatanaTM Zirconia STML and IPS e.max® ZirCAD MT Multi showed better performance compared with Ceramill® Zolid fx Multilayer. These findings suggest that increasing connector area may favor the clinical longevity of restorations.